Ab initio analysis of structural and physical properties of MgX (X=Ag, Au) alloys - Dahal, Subash; Sapkota, Dev Raj; Khadka, Denisha; Guragain, Bhupal; Chaudhary, Uchit; Yadav, Shashit (BIBECHANA, 2026)
In this study, we employed first-principles Density Functional Theory (DFT) calculations using the Perdew–Burke–Ernzerhof (PBE) pseudopotential in Quantum ESPRESSO code to investigate the structural, electronic, mechanical, vibrational, and thermodynamic properties of MgAg and MgAu intermetallic compounds. Structural optimizations confirmed that both compounds crystallize in the cubic Tetraauricupride structure with excellent agreement between the calculated lattice constants and available literature. The electronic band structures and projected density of states (PDOS) revealed the metallic nature of both compounds, with distinct orbital contributions near the Fermi level. Mechanical stability was confirmed through elastic constants satisfying the Born-Huang criteria, with MgAu demonstrating higher stiffness, lower compressibility, and slightly greater ductility compared to MgAg. Phonon dispersion relations and density of states confirmed the dynamical stability of both compounds, showing positive phonon frequencies across the Brillouin zone. Thermodynamic analyses, including vibrational free energy, entropy, heat capacities, and the Grüneisen parameter, indicated that MgAu exhibits enhanced thermal stability and stronger thermal expansion effects. The consistency between results obtained from phonon density of states and Brillouin zone integration further validates the accuracy of the predictions. These findings provide valuable insights into the potential applications of MgAg and MgAu alloys in areas such as materials design, catalysis, and electronic devices.